Mitigation of biofouling by reducing biofilm formation and extracellular polymeric substances - Muhammad Faisal, Siddiqui; Zularisam, A. W.; Mimi Sakinah, A. M. (Asian Network for Scientific Information, 2014)
Biofouling is a process of surface colonization by microorganisms via cell adhesion and production of Extracellular Polymeric Substances (EPS). It generally leads to severe problems in membrane bioreactor systems. This study addressed the feasibility of Piper betle Extract (PBE) as anti-biofouling agent against the Pseudomonas aeruginosa. The Minimum Inhibitory Concentration (MIC) (3000 μg mL-1) of PBE was selected and was used in all experiments. The anti-biofouling effects of PBE were evaluated via a microtiter plate assay and EPS production. PBE reduced biofilm formation and EPS production.